Implementasi Peraturan Gubernur Bali Nomor 1 Tahun 2020 Tentang Tata Kelola Minuman Fermentasi di Singaraja - Made Sanjaya Rama Putra; I Ketut Kasta Arya Wijaya; Luh Putu Suryani (Jurnal Preferensi Hukum, 2022)
In running an alcoholic beverage trading business, of course, you must have a permit. With the issuance of Bali Governor Regulation No. 1 of 2020 on The Governance of Fermented Beverages and/or Distillation typical of Bali aims to establish production standardization to ensure the safety and legality of fermented beverage products and or distillation, especially typical of Bali. The purpose of the research was to discuss the application of the Governor of Bali regulation number 1 of 2020 in the distribution permit of Balinese fermented drinks in Singaraja and to describe the obstacles faced in implementing the regulation of the Governor of Bali number 1 of 2020 concerning the governance of fermented Balinese wine in Singaraja. The research used the type of empirical research. This research approach uses a sociological approach and a factual approach. The sources of legal materials for this research consist of primary and secondary sources. Data collection techniques used are interview techniques and field observations. The results found that the implementation of Bali Governor Regulation Number 1 of 2020 concerning Governance of Balinese Fermented/Distilled Drinks in the distribution permit for Balinese fermented wine in Singaraja is just waiting for technical instructions, so until now the implementation in the field has not been running as it should. Obstacles encountered include monitoring efforts and still waiting for cooperation with companies that already have distribution permits.